CREATING RUBRIC TO ASSESS VOCATIONAL STUDENTS' COMPETENCE IN VIRTUAL PRACTICUM LEARNING IN BASIC ELECTRICITY SUBJECTS - Rahmadiansyah, Rifqi; Suherman, Amay (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2023)
The learning process is an effort to achieve the basic skills set out in the curriculum. In addition, assessment activities are carried out to measure and assess the level of achievement of basic skills. However, in the last 2 years, the practical learning process has been carried out online, so the assessment process with offline rubrics is less effective. Therefore, this research was conducted by making a virtual lab practicum assessment rubric with the Design Based Research (DBR) method, including 4 stages, namely; problem identification, prototype development, prototype trial and implementation, reflection for prototype. The research sample was 10 students of class X TPTU 1 SMKN 8 Bandung. The results of the rubric validity test from experts get a score of 92% with very feasible criteria, and the results of the rubric reliability test show the product is feasible to use with a reliability coefficient value of 0.644. Measurement of student competence also shows that the cognitive aspect gets 80% very good results, 10% good, and 10% sufficient, while the psychomotor and affective aspects get 100% very good results.